Antireflux Metal Stent as a First-Line Metal Stent for Distal Malignant Biliary Obstruction: A Pilot Study - Hamada, Tsuyoshi (Gut Liver, 2017)
BACKGROUND/AIMS: In distal malignant biliary obstruction, an antireflux metal stent (ARMS) with a funnel-shaped valve is effective as a reintervention for metal stent occlusion caused by reflux. This study sought to evaluate the feasibility of this ARMS as a first-line metal stent. METHODS: Patients with nonresectable distal malignant biliary obstruction were identified between April and December 2014 at three Japanese tertiary centers. We retrospectively evaluated recurrent biliary obstruction and adverse events after ARMS placement. RESULTS: In total, 20 consecutive patients were included. The most common cause of biliary obstruction was pancreatic cancer (75%). Overall, recurrent biliary obstruction was observed in seven patients (35%), with a median time to recurrent biliary obstruction of 246 days (range, 11 to 246 days). Stent occlusion occurred in five patients (25%), the causes of which were sludge and food impaction in three and two patients, respectively. Stent migration occurred in two patients (10%). The rate of adverse events associated with ARMS was 25%: pancreatitis occurred in three patients, cholecystitis in one and liver abscess in one. No patients experienced non-occlusion cholangitis. CONCLUSIONS: The ARMS as a first-line biliary drainage procedure was feasible. Because the ARMS did not fully prevent stent dysfunction due to reflux, further investigation is warranted.